Efficacy of vitamin D supplementation in the treatment of severe pneumonia in children aged less than five years - C. S., Rajshekhar; Vanaki, Raghavendra; Badakali, Ashok V.; Pol, Ramesh R.; B. C., Yelamali (International Journal of Contemporary Pediatrics, 2016)
Background: Vitamin D supplementation is useful in preventing respiratory tract infections, but there is no clear evidence to support the therapeutic efficacy of vitamin D in acute pneumonia. Methods: This study was conducted to evaluate the efficacy of vitamin D supplementation in addition to routine treatment of severe pneumonia in children less than 5 years of age. Vitamin D was supplemented at a dose of 1000 IU and 2000 IU for children <1 year and for children >1 year, respectively. Equal number of children received placebo. Results: The primary outcome was the time to resolution of severe pneumonia. Hurried breathing was present in 87.5% of drug group children and 43% of placebo group children (the difference was not significant, p=0.74).Cyanosis was present in 12.5% of children in the vitamin D group and 8.3% in children in the placebo group, with no significant difference between the treatment groups (p=0.50). Poor oral intake was reported in 22.9% cases of vitamin D group and 33.3% in placebo group. Conclusions: Short-term supplementation with vitamin D failed to show any evidence of improvement in resolution of severe pneumonia in children under the age of five.